Diethyl 6H,12H-5,11-methanodibenzo[b,f][1,5]diazocine-1,7-dicarboxylate - Bhuiyan, M. Delower H. (International Union of Crystallography, 2008)
In the molecule of the title compound, C(21)H(22)N(2)O(4), the 1,7-diethyl ester analogue of Tröger’s base, the dihedral angle between the two benzene rings is 93.16 (3)°; the molecule is C (2) symmetric.